Evaluation of narrow band ultraviolet B phototherapy in the treatment of chronic actinic dermatitis in Chinese patients. Issue 6 (19th October 2017) - Ma, Li; Zhang, Qiaoan; Hu, Yue; Luo, Xiaoqun
Abstract: Few studies have been conducted in chronic actinic dermatitis (CAD) treated with narrowband ultraviolet B (NB UVB) phototherapy, especially in Asian patients. We aim to evaluate the efficacy and safety of NB UVB phototherapy in Chinese patients with CAD. 19 CAD patients of Fitzpatrick skin phototype IV received NB UVB phototherapy in spring and treatments were given 3 times weekly with incremental dose and maintenance therapy was given twice weekly for 3–4 weeks. The mean initial, endpoint, and cumulative dose of NB UVB was 0.08, 0.33, and 6.0 J/cm 2, respectively. Patients totally received 27 times of treatments in average. 87.5% of previously ultraviolet B（UVB） sensitive patients and 75% of previously ultraviolet A（UVA） sensitive patients had normal or improved MED after phototherapy. The percentage of patients returned to normal UVB phototesting was higher than that of patients returned to normal UVA phototesting (68.8% vs. 37.5%). The mean 1‐week DLQI and the need for using immunosuppressive agents and antihistamines were significantly reduced after treatment ( p < .01 or p < .05). In conclusion, prophylactic NB UVB phototherapy is effective and safe in treatment of CAD in Chinese patients with Fitzpatrick skin phototype IV.